Evaluation of the methyl violet sorption capacity in waters with a bentonite based geopolymer material. (July 2020) - López, J A; Montaño, A M; González, C P; Medina, L
Abstract: In this study, bentonite geopolymer was used as a sorbent to remove methyl violet in aqueous solutions. Several parameters such as pH, sorbent dose and initial sorbate concentration were evaluated. The greater sorption effectiveness of bentonite geopolymer is observed at pH 2-3, and the greater sorption capacity of methyl violet by bentonite geopolymer occurs when the sorbent/sorbate ratio decreases. The study of sorption kinetics showed that the data fit the pseudo-second order model, where much of the sorption occurs during the first hour of contact, it was shown that the process prefers diffusion between pores. Sorption was adjusted to the isotherm of Langmuir, which indicated that the sorption is preferentially in monolayer. bentonite geopolymer proved to be an excellent candidate for removal of methyl violet in aqueous bodies.